THE USE OF POLYMER GEL ELECTROLYTE CONTAINING I-/I3- REDOX COUPLE TO ASSEMBLY A SOLID STATE DYE SENSITIZED TiO2 SOLAR CELL - Akhiruddin Maddu; Irmansyah Irmansyah; Mahfuddin Zuhri (Jurnal Sains Materi Indonesia, 2007)
THE USE OF POLYMER GEL ELECTROLYTE CONTAINING I-/I3- REDOX COUPLE TO ASSEMBLY A SOLID STATE DYE SENSITIZED TiO2 SOLAR CELL. A solid state dye sensitized TiO2 nanocrystalline solar cells was assembled employing a polymer gel electrolyte contains of iodide/triiodide (I-/I3-) redox couple. The use of solid electrolyte based on polymer matrix for redox ‘couples is aimed to overcome several problems of liquid cell, such as leaks of electrolyte that result in degradation of solar cell. TiO2 nanocrystalline layer was grown on TCO glass substrate by doctor blade technique was stained by synthetic dye Ruthenium 535 for a day. To complete the cell, a polymer gel based on poly(ethylene glycol) (PEG) containing I-/I3- redox couple was sandwiched between a working electrode (nanoporous TiO2 layer on conductive glass substrate) and a counter electrode (graphite sheet). The solid-state cell does not need a clipp, so the gel polymer electrolyte also acts as a glue to join the electrodes. Two cells assembled with different amount of I-/I3- redox couple used in each cell, one of cell use 20 drops of Iodolyte (contains (I-/I3- redox couple) and another cell use 30 drops of Iodolyte solution (purchased fromSolaronix, SA). The cells were characterized their photovoltaic performances included: open-circuit voltage (Voc), short-circuit current (Isc),maximum power (Pmax), fill factor (FF) and energy conversion efficiency.